Passive acoustic monitoring provides a fresh perspective on fundamental ecological questions. (6th February 2023) - Ross, Samuel R. P.‐J.; O'Connell, Darren P.; Deichmann, Jessica L.; Desjonquères, Camille; Gasc, Amandine; Phillips, Jennifer N.; Sethi, Sarab S.; Wood, Connor M.; Burivalova, Zuzana
Abstract: Passive acoustic monitoring (PAM) has emerged as a transformative tool for applied ecology, conservation and biodiversity monitoring, but its potential contribution to fundamental ecology is less often discussed, and fundamental PAM studies tend to be descriptive, rather than mechanistic. Here, we chart the most promising directions for ecologists wishing to use the suite of currently available acoustic methods to address long‐standing fundamental questions in ecology and explore new avenues of research. In both terrestrial and aquatic habitats, PAM provides an opportunity to ask questions across multiple spatial scales and at fine temporal resolution, and to capture phenomena or species that are difficult to observe. In combination with traditional approaches to data collection, PAM could release ecologists from myriad limitations that have, at times, precluded mechanistic understanding. We discuss several case studies to demonstrate the potential contribution of PAM to biodiversity estimation, population trend analysis, assessing climate change impacts on phenology and distribution, and understanding disturbance and recovery dynamics. We also highlight what is on the horizon for PAM, in terms of near‐future technological and methodological developments that have the potential to provide advances in coming years. Overall, we illustrate how ecologists can harness the power of PAM to address fundamental ecological questions in an era of ecology no longer characterised by data limitation. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.